2016
DOI: 10.22323/2.15010401
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish mass experiments — a way of encouraging scientific citizenship?

Abstract: Since 2009 Vetenskap & Allmänhet (Public & Science, VA) coordinates an annual mass experiment as part of ForskarFredag — the Swedish events on the European Researchers' Night. Through the experiments, thousands of Swedish students from preschool to upper secondary school have contributed to the development of scientific knowledge on, for example, the acoustic environment in classrooms, children's and adolescents' perception of hazardous environments and the development of autumn leaves in deciduous tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Drawing a broader and more conclusive picture building on the existing frameworks, Dick Kasperowski has described the field of citizen science as consisting of three forms, including governance discourse and research contribution: "Citizen science describes at least three things: 1) citizen science as [a] mere research method, which aims at producing scientific results. 2) citizen science as public participation, with the aim of creating legitimation for science and science policy within society 3) citizen science as citizen mobilization, with the aim of exercising legal or political influence on certain issues" (translated from Herb, 2016; see also Kasperowski and Brounéus, 2016).…”
Section: Bringing the Two Worlds Together?mentioning
confidence: 99%
“…Drawing a broader and more conclusive picture building on the existing frameworks, Dick Kasperowski has described the field of citizen science as consisting of three forms, including governance discourse and research contribution: "Citizen science describes at least three things: 1) citizen science as [a] mere research method, which aims at producing scientific results. 2) citizen science as public participation, with the aim of creating legitimation for science and science policy within society 3) citizen science as citizen mobilization, with the aim of exercising legal or political influence on certain issues" (translated from Herb, 2016; see also Kasperowski and Brounéus, 2016).…”
Section: Bringing the Two Worlds Together?mentioning
confidence: 99%
“…Nevertheless, as noted by Kasperowski and Bronéus (2016), the concept has an ambiguous meaning, where they identify two main notions, which were both conceived of in the mid-nineteen nineties, long before such developments as Web 2.0. and Zooniverse. The first refers to representative notion of citizen science that often has taken the form of deliberative initiatives, which have been implemented in the form of negotiations between various stakeholders affected by scientific knowledge, informing policy decisions (Kasperowski & Brounéus, 2016;Hagendijk & Irwin, 2006;Irwin, 1995Irwin, & 2001.…”
Section: Citizen Science and Scientific Citizenshipmentioning
confidence: 99%
“…In this more local context, citizen science becomes a strategy for citizens who are affected by these environmental issues in various ways, to influence political decision-making or legal processes. Thus, the primary objective in this second conceptualisation of citizen science is not to achieve scientific output, even though these local initiatives still rely on scientific standards -and in many cases scientific laboratories or instruments, for creating valid data (Kasperowski & Brounéus, 2016). Rather, this form of citizen science can be seen, as noted by Kullenberg (2015), as a form of resistance on behalf of citizens that can be very successful as long as it is able to produce valid scientific facts through established methods (p. 50).…”
Section: Citizen Science and Scientific Citizenshipmentioning
confidence: 99%
“…CS has been described as a potential path for participants to scientific citizenship (Cappa et al 2018;Dean et al 2018;Strasser et al 2019), that is, to an understanding of the role of science in addressing important societal issues (Kasperowski and Brounéus 2016). Moreover, there is evidence that CS leads to improved understanding and application of research methodology among citizen scientists (Bremer et al 2019;Haywood et al 2016), as well as opportunities for senior citizens to develop new skills (James and Buffel 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is evidence that CS leads to improved understanding and application of research methodology among citizen scientists (Bremer et al 2019;Haywood et al 2016), as well as opportunities for senior citizens to develop new skills (James and Buffel 2022). In addition, researchers have had ambitions that CS involvement should encourage longterm engagement in the societal issue that constitutes the research topic (Kasperowski and Brounéus 2016;Vasiliades et al 2021). Previous research has indicated that involvement in CS projects can lead to increased awareness and commitment to the societal issues at stake (Bremer et al 2019;Haywood et al 2016), although such awareness might be time limited (Jordan et al 2011).…”
Section: Introductionmentioning
confidence: 99%